2010
DOI: 10.1063/1.3327931
|View full text |Cite
|
Sign up to set email alerts
|

Flow dependence of interfacial thermal resistance in nanochannels

Abstract: In nanochannel flows, the thermal resistance at the fluid-solid interface may depend on the flow scenario. In this work, we study the interfacial thermal resistance R th in nanoscale force-driven flows at different temperatures and fluid-wall interactions. For Ar flows in Cu and Ag channels, the fluid-wall binding energy is strong and it is found that R th assumes a maximum value as the external force is varied. The maximum value is caused by the fluid adsorption on the solid surfaces and the temperature incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…For large channels, the temperature of the fluid can be much higher than the thermostat applied to the wall due to viscous frictions. 37,38 To maintain a uniform temperature in the whole system, the external force applied on the fluid molecules are carefully controlled. In nanoscale flows, fluid adsorption on solid surfaces is a popular phenomenon, which leads to new flow behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…For large channels, the temperature of the fluid can be much higher than the thermostat applied to the wall due to viscous frictions. 37,38 To maintain a uniform temperature in the whole system, the external force applied on the fluid molecules are carefully controlled. In nanoscale flows, fluid adsorption on solid surfaces is a popular phenomenon, which leads to new flow behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Torii et al showed that the energy transfer in directions parallel to the interface are governed by surface corrugations at the molecular-scale, and energy transfer in the direction perpendicular to the surface is governed by the molecular number density on solid surfaces [10]. More recently, Liu et al investigated flow dependence of the interface thermal resistance of argon in copper and silver channels, and found "solid like" behavior of argon near the walls [11]. These authors reported increased thermal resistance due to adsorption of argon on the walls.…”
Section: Introductionmentioning
confidence: 97%
“…Boundary factors originate from the solid-liquid interface, and the influence extends into the liquid bulk. These include the solid-liquid interaction [2][3][4][5][6][7][8][9][10][11][12][13][14], the commensurability of solid and liquid densities [3,4], solid structure [6,15], surface geometry [16], surface temperature [2], and so on. Bulk factors exist in the liquid bulk and the influence spreads to the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk factors exist in the liquid bulk and the influence spreads to the boundary. These include the driving force [5,[7][8][9]14], shear rate [11,13], flow rate [5,7,8], dissipation heat [10,11], liquid temperature [7], temperature gradient [2], and so on. Generally speaking, competition exists between the two types of factors at all scales, and confined liquid behavior is the consequent balance of the combined effect.…”
Section: Introductionmentioning
confidence: 99%